The Importance of Folic Acid Monitoring In Pregnancy: Implications For Maternal and Child Health in Gynecology - Augusto Ernesto Rojas Cruz; Blanca Herminia Cruz Basantes; Lino Arturo Rojas Pérez; Lino Arturo Rojas Cruz (International Journal of Medical Toxicology and Legal Medicine, 2024)
A documentary review was carried out on the production and publication of research papers related to the study of the variables FOLIC ACID, PREGNANCY and GYNECOLOGY.The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022 by Latin American institutions, achieving the identification of 55 publications. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors regarding the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that the United Kingdom with 6 publications was the country with the highest scientific production registered in the name of authors affiliated with institutions in that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material regarding the study of the different didactic methodologies for teaching in the area of general medicine was Medicine with 49 published documents, and the most used Type of Publication during the period indicated above were Journal Articles with 82% of the total scientific production.